THE INFLUENCE OF AUDIO-VISUAL MEDIA ON STUDENTS LEARNING MOTIVATION DURING THE PANDEMIC TIME OF COVID-19 AT MI AL FAJAR PRINGSEWU - Faradila, Sinta; Umurohmi, Ulfah; Muhtarom, Muhtarom; Hamid, Abdul (STIT AL MULTAZAM, 2021)
The Covid 19 outbreak has an impact on various areas of life, especially the world of education. Student learning is required to transform and adapt to the conditions of the 4.0 century. This is what motivates researchers to conduct research on children's learning motivation during the Covid-19 pandemic. The aim of this research is to determine the effect of using audio-visual media on student motivation during the Covid-19 pandemic in grade IV MI Al Fajar Pringsewu. This research is a quantitative study with data collection techniques using a questionnaire. The data were analyzed using a simple linear regression test. The results of this study indicate there is an effect of audiovisual media on student learning motivation during the Covid-19 pandemic with a known value tcount > ttable (4.118 > 2.056) then Ho was rejected and Ha accepted. The big influence of audio-visual media on student learning motivation namely 57,3 %